2015
DOI: 10.1007/s00431-015-2566-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epidemiology and clinical characteristics of infections by human parechovirus vs. those by enterovirus during the first month of life

Abstract: Human parechoviruses (HPeV) have been recently recognized as important viral agents in paediatric infections. The aims of this study were to investigate the HPeV infection prevalence in infants <1 month in Spain and, secondly, to analyse the clinical and epidemiological characteristics of the infected patients compared with those infected by enterovirus (EV). Infants <1 month with neurological or systemic symptoms were included in a multicentre prospective study. EV and HPeV detection by RT-PCR and genotyping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 26 publications
7
53
0
2
Order By: Relevance
“…EV peaked in August and September and was detected over a longer term than HPeV. The seasonal characteristics are similar to those in recent studies …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…EV peaked in August and September and was detected over a longer term than HPeV. The seasonal characteristics are similar to those in recent studies …”
Section: Resultssupporting
confidence: 89%
“…In the present study the viral epidemiology of febrile infants aged <3 months near Tokyo, Japan was clarified (Table ). The prevalences of HPeV and EV of 19.6% and 30.4%, respectively, noted in the present study were similar to the 10.7% and 38.1% found in a recent Spanish study of infants up to 1 month of age using CSF, sera and throat swabs . Few reports have assessed the prevalence in Asia …”
Section: Discussionsupporting
confidence: 91%
“…Only 18% had a predominance of lymphocytes. Studies investigating blood CRP have found a median (IQR) range of 17 (7–26) mg/L10 and 6 (4–13) mg/L11 and a mean (SD) of 10.8 (27) mg/L 12. The study by Sormunen et al 13 found that 93% of infants had a CRP <20 mg/L and the maximum CRP was 40 mg/L, and in the study by Michos et al 3 the CRP was <20 mg/L in 84% of patients (note units in the referenced published article were stated as mg/dL due to a typographical error).…”
Section: Are the Crp Or Blood Wcc Abnormal In Ev Meningitis/encephalimentioning
confidence: 99%
“…En los exámenes de laboratorio general destacaron parámetros inflamatorios bajos, leucopenia y aumento de transaminasas, en el contexto de un cuadro viral, lo que ha sido reportado en estudios previos 32,35 . El paciente con HPeV positivo en LCR, presentó un análisis citoquímico de líquido cefalorraquídeo normal para la edad la cual es una de las diferencias descritas al comparar meningoencefalitis por HPeV con EV 37,38 . En el contexto clínico y de laboratorio presentado existe un patrón de sospecha que debe confirmarse con un diagnóstico virológico específico.…”
Section: Artículo Originalunclassified